Essays on Energy and Environmental Economics - Qi, Qi. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Economics.; Advisor: Kelly Gallagher.; Committee: Ujjayant Chakravorty, and Shinsuke Tanaka.; Keyword: Environmental economics.